Rancang Bangun Sistem Pengukuran Indikator Pelayanan Pasien Rawat Inap Untuk Peningkatan Mutu Layanan Puskesmas Menggunakan Rumus IPRI - Ali Tarmuji; Cantya Dhanurendra (STMIK Budi Darma, 2022)
Health agency service indicators are used to determine the level of utilization, quality, and efficiency of health agency services. The measurement of service indicators is determined by applying the correct IPRI (Indicator of Inpatient Service) method/formula. Based on the results of observations in the Medical Record unit of the Berbah Public Health Center, Sleman Yogyakarta, it was found that the delay in returning the daily inpatient census sheets affected the value of each service indicator. In addition, inaccuracy in calculating the daily inpatient census data recapitulation resulted in inaccurate data. Therefore, a computer-based inpatient service indicator measurement system is needed in order to produce a faster and more accurate value for each service indicator in inpatient services. The stages of the research carried out adopted the stages in the SDLC Waterfall method, including the first stage of communication (project initiation & requirement gathering). The second stage is planning (estimating, scheduling, tracking). The third stage of modeling (analysis & design). The fourth stage of construction (code & test). The last stage, deployment (delivery, support, feedback). The application of the IPRI method/formula in PHP coding and supported by MySQL DBMS storage is part of the construction phase which is combined with testing using the black box test and alpha test methods. The goal has been achieved with the establishment of the Service Indicator Measurement System Application based on IPRI in inpatient services at the Berbah Health Center, Sleman Yogyakarta. The system is categorized as good and feasible to use based on the results of black box testing of 84.62% true. Alpha testing obtained a very high level of acceptance (approved) of 100%. The use of this application is proven to be able to produce IPRI calculations quickly and accurately so as to improve the quality of inpatient services, especially related to the daily census, so that leaders can make decisions faster.